Podoplanin - a small glycoprotein with many faces - Ugorski, Maciej (Am J Cancer Res, 2016)
Podoplanin is a small membrane glycoprotein with a large number of O-glycoside chains and therefore it belongs to mucin-type proteins. It can be found on the surface of many types of normal cells originating from various germ layers. It is present primarily on the endothelium of lymphatic vessels, type I pneumocytes and glomerular podocytes. Increased levels of podoplanin or its neo-expression have been found in numerous types of human carcinomas, but it is especially common in squamous cell carcinomas, such as cervical, larynx, oral cavity, skin and lung cancer. This small sialomucin is also seen on the surface of cancer-associated fibroblasts (CAFs) in lung adenocarcinomas, as well as in breast and pancreatic tumors. In most cancers, a high level of podoplanin expression, both in cancer cells, as well as in CAFs, is correlated with an increased incidence of metastasis to lymph nodes and shorter survival time of patients. Little is known about the biological role of podoplanin, however research carried out on mice with a knock-out gene of this glycoprotein shows that the presence of podoplanin determines normal development of lungs, the lymphatic system and heart. Podoplanin on cancer cells and CAFs seems to play an important role in the development and progression of various cancers. However, its role in these processes is both unclear and controversial. In this review, the role of podoplanin in both physiological processes and carcinogenesis is discussed.